(Be)coming Home An Existential Perspective on Migration, Settlement and the Meanings of Home (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
This paper draws on research into the meanings of home as experienced and constructed by a number of voluntary migrants. It offers a theoretical discussion of the concept of home, relating this to the contrast between Heidegger's earlier and later thoughts on the idea of home. The research findings are presented in a Kierkegaardian framework which draws parallels between changes in the meaning of home and the development of the self.
Keywords: Home; migration; settlement; heidegger; kierkegaard; alienation; belonging